Ultrasound Aided Expedient Synthesis, Characterization and Antimicrobial Studies of Fluorenyl-Hydrazono-Thiazole Derivatives - Kaur, Avneet Pal; Gautam, Deepika (Asian Journal of Chemistry, 2019)
Ultrasound assisted facile synthesis of fluorenyl-hydrazonothiazoles (4a-d) in quantitative yields by the condensation of 2-(9H-fluoren-9-ylidene)hydrazinecarbothioamide (2) with substituted phenacyl bromides in presence of dimethyl formamide has been reported. The reaction of carbothioamide 2 with α-haloacids resulted in to fluorenyl-hydrazonothiazolidin-4-ones (3). The structural characterization of the cyclized products have been established by elemental analysis and spectral data (IR, NMR and mass). The antimicrobial studies of the synthesized compounds are also reported.